Carbon dynamics, net primary productivity and human‐appropriated net primary productivity across a forest–cocoa farm landscape in West Africa. (6th June 2019) - Morel, Alexandra C.; Adu Sasu, Michael; Adu‐Bredu, Stephen; Quaye, Marvin; Moore, Christine; Ashley Asare, Rebecca; Mason, John; Hirons, Mark; McDermott, Constance L.; Robinson, Elizabeth J. Z.; Boyd, Emily; Norris, Ken; et al.
Abstract: Terrestrial net primary productivity (NPP) is an important metric of ecosystem functioning; however, there are little empirical data on the NPP of human‐modified ecosystems, particularly smallholder, perennial crops like cocoa ( Theobroma cacao ), which are extensive across the tropics. Human‐appropriated NPP (HANPP) is a measure of the proportion of a natural system's NPP that has either been reduced through land‐use change or harvested directly and, previously, has been calculated to estimate the scale of the human impact on the biosphere. Additionally, human modification can create shifts in NPP allocation and decomposition, with concomitant impacts on the carbon cycle. This study presents the results of 3 years of intensive monitoring of forest and smallholder cocoa farms across disturbance, management intensity, distance from forest and farm age gradients. We measured among the highest reported NPP values in tropical forest, 17.57 ± 2.1 and 17.7 ± 1.6 Mg C ha −1 year −1 for intact and logged forest, respectively; however, the average NPP of cocoa farms was still higher, 18.8 ± 2.5 Mg C ha −1 year −1, which we found was driven by cocoa pod production. We found a dramatic shift in litterfall residence times, where cocoa leaves decomposed more slowly than forest leaves and shade tree litterfall decomposed considerably faster, indicating significant changes in rates of nutrient cycling. The average HANPP value for all cocoa farms was 2.1 ± 1.1 Mg C ha −1 year −1 ; however, depending on the density of shade trees, it ranged from −4.6 to 5.2 Mg C ha −1 year −1 . Therefore, rather than being related to cocoa yield, HANPP was reduced by maintaining higher shade levels. Across our monitored farms, 18.9% of farm NPP was harvested (i.e., whole cocoa pods) and only 1.1% (i.e., cocoa beans) was removed from the system, suggesting that the scale of HANPP in smallholder cocoa agroforestry systems is relatively small. Abstract : Terrestrial net primary productivity (NPP) is an important metric of ecosystem functioning; however, there is little empirical data on the NPP of human‐modified systems like smallholder agriculture, which is extensive across the tropics. This study presents the results of 3 years of intensive monitoring of forest and cocoa farms across disturbance and management intensity gradients. We found the average NPP across our monitored cocoa farms was higher than measured forest, particularly driven by cocoa pod production, which appeared to be similar across the tropics using forest and cocoa NPP values reported in the literature.